Interactive Learning Media Development Based on Android Assisted by Google Sites on Building Static Calculation Element in 2nd Depok National Vocational High School - Niken Rarasati; Affero bin Ismail (Jurnal Pendidikan Teknik Sipil, 2023)
Background:  This study aims to develop interactive learning media based on android assisted by Google Sites on building static calculation element class X SMK N 2 Depok and to determine the feasibility of the media in terms of material and media aspects.Methods: The research is Research and Development (R&D) method using waterfall model development. The stage of waterfall model are analysis, design, coding, testing, and maintenance. Data is collected using interviews, questionnaires, and device usage. Feasibility data analysis using category range analysis.Results:  The results of this research according to the stages (1) the analysis stage reveals problems with learning methods and models that are not yet sufficient for students to learn according to the independent learning curriculum. The software used is Adobe Illustrator and assisted by Google Sites with an android smartphone v4.1 has a minimum of 1GB of RAM and 1GB of free memory. (2) The design stage uses UML planning and storyboards. UML diagrams include use case, activity, class, and sequence. (3) The coding stage is assisted by Google Sites using Markup Language HTML and Website Appsgeyser. (4) The testing phase is carried out on material and media aspects according to ISO 25010. (5) The maintenance stage involves improving the appearance and explanation of the questions.Conclusion:  Based on the test results it is concluded that the media developed is feasible to use.